Legal Analysis Of Restorative Justice In The Settlement Of Theft Cases Based On Prosecutor's Regulation No. 15 Of 2020 And Islamic Law - Andry Syafrizal Tanjung; Beby Sendy; Gian Randa Juangsah (International Journal of Society and Law, 2025)
The law is made to maintain a balance between the interests of individuals, groups and other living beings. The Attorney General of the Republic of Indonesia has issued Regulation of the Attorney General of the Republic of Indonesia Number 15 of 2020 concerning the Termination of Prosecutions Based on Restorative Justice, this is to provide solutions to problems in handling cases for theft crimes regulated in the regulation. In Islamic law, the settlement of cases of theft can also be resolved by peace based on justice, this is based on the Qur'an, Ash-Shuraa': 40 and the Qur'an surah al-nisaa‟ verse 149.